Socio Emotional Wealth Approach and Corporate Social Responsibility Disclosure in Indonesia - Ni Made Adi Erawati; Dewa Gede Wirama; Endra Kartika Yudha (Universitas Pendidikan Ganesha, 2024)
This study aims to demonstrate that corporate governance moderates the effect of family ownership on Corporate Social Responsibility (CSR) disclosure. This research employs an archival approach, utilizing content analysis, in-depth discussions, observations, and secondary data. The sample consists of family-owned companies (Family Business Enterprises) within the manufacturing industry, selected using a purposive sampling method. The data were tested and analyzed using SPSS. The results indicate that family ownership has a positive effect on CSR disclosure. Moreover, corporate governance can enhance the positive influence of family ownership on CSR disclosure. These findings support the Socio-Emotional Wealth Theory, suggesting that family companies are more likely to prioritize CSR disclosure to preserve the family name and prestige. The study contributes to the accounting literature by highlighting the interplay between family ownership, corporate governance, and CSR practices. It provides valuable insights for policymakers and practitioners, emphasizing the importance of robust corporate governance structures in promoting transparency and accountability in family-owned businesses. By understanding these dynamics, stakeholders can better appreciate the motivations behind CSR disclosures in family firms and work towards fostering a more socially responsible corporate environment.